2010
DOI: 10.1177/0963662509356502
|View full text |Cite
|
Sign up to set email alerts
|

Framing and sources: a study of mass media coverage of climate change in Peru during the V ALCUE

Abstract: Studies about mass media framing have found divergent levels of influence on public opinion; moreover, the evidence suggests that issue attributes can contribute to this difference. In the case of climate change, studies have focused exclusively on developed countries, suggesting that media influence perceptions about the issue. This study presents one of the first studies of media coverage in a developing country. It examines newspapers' reporting in Peru during the Fifth Latin America, Caribbean and European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 46 publications
(57 reference statements)
4
49
0
2
Order By: Relevance
“…For example, in the journal Brazilian Journalism Research, out of the 50 articles on journalism published between 2005 and 2008, only five focused on the news conveyed by the TV 7 . When searching for papers on science and technology content in the newscasts, the number of Brazilian research publications is even smaller, with most papers dealing with science coverage in general in the foreign printed press 8,9,10,11,12 or with specific scientific issues such as nanotechnology, 13,14 biotechnology, 16,17,18 and climate change, 19,20,21,22,23 mostly in foreign media. The identification of the position occupied by science in the media, particularly television, would make it possible to check to what extent Brazilians' demand for this kind of information is met.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the journal Brazilian Journalism Research, out of the 50 articles on journalism published between 2005 and 2008, only five focused on the news conveyed by the TV 7 . When searching for papers on science and technology content in the newscasts, the number of Brazilian research publications is even smaller, with most papers dealing with science coverage in general in the foreign printed press 8,9,10,11,12 or with specific scientific issues such as nanotechnology, 13,14 biotechnology, 16,17,18 and climate change, 19,20,21,22,23 mostly in foreign media. The identification of the position occupied by science in the media, particularly television, would make it possible to check to what extent Brazilians' demand for this kind of information is met.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the media coverage of controversial topics have revealed that manipulation of information in the media generally aims to benefit more powerful groups (Herman and Chomsky, 1988). This suggests that the government mainly decides what the media reports (Takahashi, 2011). Therefore, this study attempts to further examine government's impact on the media.…”
Section: Introductionmentioning
confidence: 98%
“…The body of literature is growing significantly, for example, in the United States (see Antilla, 2005;McComas & Shanahan, 1999;, the United Kingdom (Garvin, 2009;Carvalho, 2005;Carvalho & Burgess, 2005;Taylor & Nathan, 2002), British Columbia in Canada (Gunster, 2011), France (Brossard, Shanahan & McComas, 2004), New Zealand (Wilson, 2000;Dispensa & Robert, 2003;Kenix, 2008), Australia (Bacon, 2011;Henderson-Sellers, 1998;McManus, 2000), Japan (Sampei and Aoyagi-Usui, 2009), Peru (Takahashi, 2010), Finland (Dispensa & Robert, 2003), Spain (Leon et al, 2011), India (Boykoff, 2010) among others. These studies examine diverse aspects of journalism such as objectivity, norms, bias, structure (Boykoff, 2007a(Boykoff, , 2007bBoykoff andBoykoff, 2004, 2007;Shanahan & Good 2000;Smith, 2005) and media framing (Antilla, 2005;Takahashi, 2010) and examine the weaknesses and strengths of media coverage in the West (Boykoff & Roberts, 2007), with a few studies focused on foreign media reporting about low lying islands (Day, 2010;Cameron, 2011).…”
Section: Research On Media Coverage Of Climate Changementioning
confidence: 99%